2019
DOI: 10.1183/13993003.01563-2018
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity pneumonitis and its correlation with ambient air pollution in urban India

Abstract: Hypersensitivity pneumonitis (HP) is an immune-mediated lung disease (ILD) caused by sensitisation to inhaled organic antigens or low molecular weight chemical compounds. Recently, there has been increased awareness of environmental factors associated with HP [1]. It has been postulated that when genetically susceptible individuals ("first hit") are exposed to an inciting antigen ("second hit") they develop HP [2]. The first hit is essential, as not all who are exposed to an inciting antigen develop disease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 11 publications
(13 reference statements)
0
22
0
4
Order By: Relevance
“…the exposure to causative antigen—alone cannot induce HP development (Spagnolo et al 2015 ). A recent study has indicated an association between air pollution level and HP occurrence in India (Singh et al 2019 ). It is apparent that air pollution could be a risk factor for HP, but how air pollution could influence HP pathogenesis is largely unknown.…”
Section: Air Pollution and Epigenetic Modifications In Hypersensitivity Pneumonitis (Hp)mentioning
confidence: 99%
See 1 more Smart Citation
“…the exposure to causative antigen—alone cannot induce HP development (Spagnolo et al 2015 ). A recent study has indicated an association between air pollution level and HP occurrence in India (Singh et al 2019 ). It is apparent that air pollution could be a risk factor for HP, but how air pollution could influence HP pathogenesis is largely unknown.…”
Section: Air Pollution and Epigenetic Modifications In Hypersensitivity Pneumonitis (Hp)mentioning
confidence: 99%
“…The study demonstrates that the odds of developing HP is 7% greater for every 10 μg/m 3 increase in air pollution (PM2.5 level). The authors hypothesize that fine-particulate air pollutants lead to airway inflammation, reduce mucociliary clearance in the alveoli, and lead to an immune-mediated response that ultimately leads to the development of HP (Singh et al 2019 ). It is apparent that more rigorous studies are necessary to establish this hypothesis.…”
Section: Air Pollution and Epigenetic Modifications In Hypersensitivity Pneumonitis (Hp)mentioning
confidence: 99%
“…On the other hand, exposure to damaging agents, such as cigarette smoke, air pollution, viral infections, and pesticides also influences the development of the disease as well as the heterogeneous behavior (2,3,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiology study using HP data from 2004 to 2013 in U.S. showed that approximately one-fourth HP cases were brotic HP, which were related to a higher mortality rate [3]. Reports showed that increasing HP incidence was associated with urban air pollution [4]. The gradually increased morbidity of those organic dust-induced disease was not only related to its wildly existence in living environment, but also because more and more occupational environments were at risk of organic dust exposure.…”
Section: Introductionmentioning
confidence: 99%